PERAN WARGA SEKOLAH DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK - Al Hudri; Hunainah Hunainah (QATHRUNÂ, 2021)
This study aims to determine the role of school residents in the formation of the religious character of students in Al Husna Islamic Elementary School and Al Qudwah Elementary School. This study uses a qualitative approach with the type of field research (field research). The research was conducted in two places, namely (1) Al Husna Rangkasbitung Islamic Elementary School and Al Qudwah Integrated Elementary School Kalanganyar. Data were collected by in-depth interviews, observation, and documentation. The results of this study are; (1) religious character is needed and must be possessed by students to face changing times and moral degradation. The formation of religious character can be assessed from the aspect of the spiritual attitude of students. (2) the role of school residents such as principals, teachers and parents is very important in shaping the character of students, educators as second parents in schools are the main motor in shaping the religious character of students. (3) the role of parents cannot be underestimated in an education, students who spend more time at home ideally parents should be able to synergize in the formation of the religious character of students when at home. (4) inhibiting factors for the formation of religious character in Islamic schools, one of which is educational policies that are not in line with the school program. (5) efforts are being made to optimize the formation of religious characters by providing education and training for teachers around character building, appreciation of students and parental liaison books.